The time profile of transformations in territorial governance: Towards a meeting point between urban planning and risk management - Talia, Michele (TeMA - Journal of Land Use, Mobility and Environment, 2021)
As a result of the close relationship with the School of Architecture founded in 1919, Italian urban planning has often been marked by a search for a difficult balance between spatial and temporal projections in plans, often favouring the former over the latter. Due to this unequal development in planning contents, territorial governance has shown a worrying loss of authority, which tends to generate evident contradictions when territorial planning is called to contend with problems deriving from the management of areas where urban planning forecasts must coexist with extraordinary provisions adopted following an earthquake or other natural disaster. In this recurring difficulty of finding space within ordinary planning procedures for measures designed to address the emergency, three starting conditions prove to be decisive. The first is the need to guarantee the availability of a rigorous cognitive framework to allow an increasingly complex planning system to be based on rich, detailed information. The second is the requirement to reduce the gap between the technical times necessary to develop planning tools and the necessary promptness for procedures to coordinate emergency policies. The third is the need to entrust strategic documents with the task of balancing the relationship between the short and long terms, both in urban planning and in emergency plans.